Multiple personality dis(ordered) - Ab Kadir, Sarah (2012)
Multiple personality dis(ordered) is an installation which developed from the idea of how people generally please others in order to adapt. This sense of belonging will forever be. Everyone rubs off traits from each other to become somewhat similar to the next person beside them. The outcome is a sculpture, placed in the center of the room. Live feedback images of the faces of the audience are traced and projected onto the sculpture with the use of hidden webcams. Over time, the images disappear and make way for new faces, reflecting on how people lose and pick up certain traits.